A multi-omics view of the preservation effect on Camellia sinensis leaves during low temperature postharvest transportation. (15th March 2023) - Chen, Jiahao; Mei, Shuang; Zheng, Peng; Guo, Jiaming; Zeng, Zhixiong; Lu, Huazhong; Sun, Binmei
Abstract: Appropriate postharvest conditions protect freshly harvested plant products, preventing substantial economic losses. In this study, the effects of low temperature transportation on postharvest tea leaves were studied with widely targeted secondary metabolomics and transcriptomics. Compared with non-refrigerated tea leaves (30 ± 3 °C), there were 67-up and 41-down differentially regulated metabolites in refrigerated tea leaves (8 ± 2 °C), mainly consisting of flavonoids, amino acids, and purine alkaloids. The change of flavonoids was primarily due to degradation and differential accumulation, while the refrigerated environment effectively maintained galloylated catechins at a relatively high level. Branched-chain amino acids significantly increased in non-refrigerated condition, while purine alkaloids and their precursors showed a trend of accumulation in refrigerated condition. These differences were attributed to genes directly related to the metabolite revealed by RNA-seq analysis, as well as to the hub transcription factors (such as DOF and AP2/ERF ) that related to response of environmental fluctuations explored by co-expression network. These important metabolites regulation mechanisms under low-temperature postharvest transportation will provide valuable information for optimizing postharvest transportation parameters and maintaining tea quality. Highlights: Using multi-omics approach to explore tea leaves postharvest transportation effect. Flavonoids and amino acids were most sensitive to environmental fluctuations. Refrigerated environment effectively maintained galloylated catechins in a relative high level.